2014
DOI: 10.17219/acem/37045
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics of the Triceps Brachii Muscle in the Human Fetus

Abstract: Background. The triceps brachii muscle, the strongest extensor of the elbow joint, is characterized by the three heads: long, lateral and medial. Objectives. In the present study we aimed to examine the linear parameters (length, width) of the fetal triceps brachii muscle and to provide their growth dynamics. Material and Methods. Using anatomical dissection, digital image analysis (Multiscan v.14.02), and statistics (Student's t-test, regression analysis) we measured in mm the length and width of the triceps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
4
7
0
Order By: Relevance
“…In accordance with the previous study results on morphometric properties of different muscle groups [2,4,13,14,17], this study revealed a rational increase in numerical values of TFL surface area, width and lengths from 18 th to 30 th week and showed no statistically significant difference between sides and sexes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the previous study results on morphometric properties of different muscle groups [2,4,13,14,17], this study revealed a rational increase in numerical values of TFL surface area, width and lengths from 18 th to 30 th week and showed no statistically significant difference between sides and sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Although literature reported a number of differences in many muscle growth dynamics between fetuses [2,4,13,14,17,25], no quantitative studies on TFL were…”
Section: Discussionmentioning
confidence: 99%
“…Neither sexual dimorphism nor asymmetry was very characteristic. Other observations based on less material comprising a smaller age span (Badura et al 2011a, b; Grzonkowska et al 2014; Szpinda et al 2011, 2013) revealed similar results.…”
Section: Introductionsupporting
confidence: 57%
“…1) present parameters of analysed monoequation, biparametric ( b 0 and b 1 ) mathematical models for CRL of the trunk ( verte - tuberale ). Approximation was made on the basis of CRLs included in Scammon’s and Calkins’ tables (Bożiłow and Sawicki 1980; Grzonkowska et al 2014). Extrapolation of a linear model from the first weeks of life results in negative values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They found no sex differences, which is in line with our current study. Furthermore, numerous morphometric studies on skeletal muscles in the human fetus, including triceps brachii [23], biceps brachii [24], deltoid [25], semitendinosus [26], semimembranosus [27], and biceps femoris [28] indubitably divulged no significant male-female differences. Not even once did we notice any laterality differences in the material under examination.…”
Section: Discussionmentioning
confidence: 99%